2023
DOI: 10.1111/cea.14311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of evidence of treatment effects in randomized and nonrandomized studies on allergen immunotherapy

Abstract: Nonrandomized studies (NRS) on allergen immunotherapy (AIT) particularly lend themselves to evaluate outcomes that are insufficiently addressed in randomized controlled studies (RCTs). However, NRS are prone to several sources of bias, which limit their validity. We aimed at comparing AIT effects between RCTs and NRS and evaluate the reasons for discrepancies in study results. In this analysis, we compared NRS on AIT (including subcutaneous and sublingual immunotherapy, SCIT and SLIT, respectively) with SLIT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(154 reference statements)
0
5
0
Order By: Relevance
“…While the level of evidence of observational data is considered low compared to randomised controlled trials (RCTs), several comparative studies have shown that outcomes of RCTs and observational studies are comparable in terms of treatment effect and quality [ 22 24 ]. Nevertheless, a recent meta-analysis showed that the risk of bias was directly correlated with the effect estimate [ 25 ]. Therefore, the choice of a robust primary outcome measure, inclusion criteria, and prospective data collection are essential in reducing the risk of bias [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the level of evidence of observational data is considered low compared to randomised controlled trials (RCTs), several comparative studies have shown that outcomes of RCTs and observational studies are comparable in terms of treatment effect and quality [ 22 24 ]. Nevertheless, a recent meta-analysis showed that the risk of bias was directly correlated with the effect estimate [ 25 ]. Therefore, the choice of a robust primary outcome measure, inclusion criteria, and prospective data collection are essential in reducing the risk of bias [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many meta-analysis and reviews outlined that major limitation in evaluating the clinical outcome of AIT are the broad diversity in composition of products, the study designs, the heterogeneity of the environmental conditions, the age of the population involved and the use of different primary and secondary study endpoints ( 88 , 94 , 95 ). Moreover, different outcomes have been reported between SLIT and SCIT, as well as between SLIT delivered by tablets or by drops ( 88 ).…”
Section: Effectiveness Of Allergic Immunotherapymentioning
confidence: 99%
“…Allergen immunotherapy (AIT) remains one of the most important treatment methodologies in contemporary allergology [1 & ,2,3]. Its efficacy in treating allergic rhinitis, some forms of asthma, and allergies to Hymenoptera venoms and selected foods has been confirmed in many clinical randomized and nonrandomized trials, reports, and meta-analyses, [4][5][6][7][8][9][10][11]. Qualification criteria, contraindications, routes of administration, and the assessment of safety and efficacy depending on the desensitized allergens are included in many international consensuses, most importantly, in the European Academy of Allergy and Clinical Immunology (EAACI) recommendations [6,10,12,13].…”
Section: Introductionmentioning
confidence: 99%